Assessing the Relationship Between ICT Integration and Academic Performance Among University Students in Andahuaylas, Peru - Cárdenas-Solano, Johel; Flores-Ccorisapra , Yovana; Oré-Cerrón, Juan José; Gutiérrez-Aparco, Julián; Surichaqui-Mateo, Abad Antonio; Palomino-Román, Filomón; Hancco-Gomez, Miriam Serezade; Salazar-Espinoza, Jaime Rodrigo; Huarcaya-Taype, Rosaura; Cruz-Atamari, Rocio (Journal of Posthumanism, 2025)
This study investigates the impact of Information and Communication Technology (ICT) integration on the academic performance of university students at the University of the Andes in Andahuaylas, Peru, during 2023. Surveys were used to evaluate the utilization of ICT tools including forums and tasks and videoconferencing in a study involving 140 university students. The research data indicates that 64.3% of participants demonstrated advanced skills in ICT integration and 79.3% exhibited high task participation. Academic performance displayed a substantial positive link to ICT integration based on the analysis results (r = 0.895, p < 0.01). The data indicates that students who use forums generate the highest impact on their academic performance based on a coefficient of 0.238 (p < 0.000). The current analysis demonstrates that task engagement values contributed significantly (p < 0.000) along with a coefficient value of 0.201. Academic performance shows improved results with ICT tools specifically forums and tasks and this discovery redefines educational strategy development as well as digital tool execution in higher education settings.